1994
DOI: 10.1192/bjp.165.2.160
|View full text |Cite
|
Sign up to set email alerts
|

A National Audit of New Long-Stay Psychiatric Patients

Abstract: Despite the continued policy of bed closures and focus on care in the community, some patients admitted recently to psychiatric units in the UK still have protracted hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…This fi nding is confi rmed by a recent survey of the new long-stay population (Lelliott et al, 1994).…”
Section: Discussionsupporting
confidence: 62%
“…This fi nding is confi rmed by a recent survey of the new long-stay population (Lelliott et al, 1994).…”
Section: Discussionsupporting
confidence: 62%
“…A more recent national audit of 'new long-stay' inpatients (Lelliot et al, 1994) confirmed that this population was continuing to accumulate in spite of substantial reductions in long-stay bed numbers by this time. The accumulation of these patients was reducing the availability of acute beds for emergency admissions, and their impact upon services was 'disproportionate to their number because of the nature and severity of their disabilities and behavioural problems' (Lelliot et al, 1994). These authors highlighted the similarities between this 'new long-stay' population and the 'forensic' population of predominantly young men suffering from schizophrenia, detained under the Mental Health Act 1983, often with a history of violence and criminality.…”
Section: The 'New Long-stay' Problemmentioning
confidence: 81%
“…For example, the HDU sample were younger than an 'old long-stay' sample (O'Driscoll and Leff, 1993) and on the SBS there is a trend for HDU patients to have fewer problems with hygiene but more problems with hostility. Compared with a 'new long-stay' population (Lelliot et al, 1994), the HDU patients were more likely to have an origin of admission patients' at Friern and Claybury hospitals, H D U patients were younger but the proportion of patients with schizophrenia, and the scores on the SBS subscale for destructiveness and inappropriate sexual behaviour, were similar (Trieman andLeff, 1996a, 1996b).…”
Section: Discussionmentioning
confidence: 93%
“…However, initial hopes of totally eliminating the long-stay inpatient populations were dampened with the recognition that 'new long-stay patients' or 'new chronics' were accumulating (Magnus, 1967;Wing and Furlong, 1986;Lelliot et al, 1994) and that there was a group of patients for whom transfer to the community was neither possible nor desirable, the so-called 'difficult to place' patients (Mann and Cree, 1976;Coid, 1991). There were various problems encountered in the management of these patients including lack of patient co-operation, fragmentation of hospital care and aftercare, and geographical drift (McClelland and Kerr, 1991).…”
Section: The H I G H D E P E N D E N C Y N E T W O R Kmentioning
confidence: 97%